Función de los brasinoesteroides en el crecimiento fisiológico del cultivo de café (Coffea arábica) - Fajardo Morán, Odalis Mabel (2022)
Coffee (Coffea Arabica) is a crop that requires proper management to increase its yield and quality. Therefore, it is essential that producers have knowledge of the functions of the application of brassinosteroids, for the optimal growth of coffee crops. Despite the excellent advantages of the application of growth regulators in crops, there is still a lack of knowledge of the benefits provided by Brassinosteroids in the processes of growth and development of plants. For this reason, the objective of this case study is to characterize the function of brassinosteroids in the physiological growth of the coffee crop (Coffea Arábica). The methodology used in the research has a non-experimental design, the types of research used were descriptive and bibliographic because it seeks to describe the phenomenon and analyze it by accessing various sources of information; while the method was inductive. Through the analysis of the information collected through the various bibliographic sources, the following results were obtained: One of the first findings identified is that the cultivation of coffee is of great importance since it generates innumerable benefits for both farmers and consumers; however, there are factors that alter its production and quality. Therefore, it is necessary to make use of alternatives that help improve its performance and quality. The use of brassinosteroids in crops is essential since one of its main functions is to stimulate the physiological growth and development of plants.